2004
DOI: 10.1111/j.1472-8206.2004.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose levels observed in daily clinical practice induce endothelial dysfunction in the rabbit macro‐ and microcirculation

Abstract: We investigated whether different concentrations of elevated glucose - corresponding to levels observed in patients with type 2 diabetes under routine care (post-prandial mean and maximum values) and those used for diagnosing diabetes - induce impairment of vascular reactivity of the macro- and microcirculation in non-diabetic rabbits. Aortic rings and isolated perfused kidneys from normal rabbits were acutely exposed (3 h) to normal (5.5 mm) or high (7-25 mM) D-glucose concentrations. Vascular reactivity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 32 publications
2
24
0
4
Order By: Relevance
“…According to such "in vitro" evidence, we can hypothesize that tight control in postprandial glucose excursions, such as that observed after repaglinide treatment, can improve endothelial function and decrease oxidative stress, thus contributing to a decline of cardiovascular disease risk in type 2 diabetic patients. Our data showing that repaglinide-but not glibenclamide-administration is associated with a significant improvement in 2-h postprandial glucose levels, the degree of oxidative stress, and brachial reactivity are in agreement with previous in vitro data (25)(26)(27). In addition, the relationship between changes in 2-h plasmaglucose levels and brachial reactivity is independent of the main metabolic parameters but is dependent on the TBARS and TEAC levels.…”
Section: Cardiovascular Datasupporting
confidence: 82%
See 1 more Smart Citation
“…According to such "in vitro" evidence, we can hypothesize that tight control in postprandial glucose excursions, such as that observed after repaglinide treatment, can improve endothelial function and decrease oxidative stress, thus contributing to a decline of cardiovascular disease risk in type 2 diabetic patients. Our data showing that repaglinide-but not glibenclamide-administration is associated with a significant improvement in 2-h postprandial glucose levels, the degree of oxidative stress, and brachial reactivity are in agreement with previous in vitro data (25)(26)(27). In addition, the relationship between changes in 2-h plasmaglucose levels and brachial reactivity is independent of the main metabolic parameters but is dependent on the TBARS and TEAC levels.…”
Section: Cardiovascular Datasupporting
confidence: 82%
“…In addition, cultures of porcine aortic endothelial cells (PAECs) submitted to high-glucose concentrations showed an endothelial dysfunction mediated by hyperglycemia, which was revealed by reduced endothelial NO production or release (22)(23), as well as severe changes in endothelial cell structure (24). More recently, several studies suggested plasma glucose fluctuations and glucose peaks, such as those occurring in the postabsorptive state, to provide a strong contribution to the development of endothelial dysfunction (25)(26)(27). According to such "in vitro" evidence, we can hypothesize that tight control in postprandial glucose excursions, such as that observed after repaglinide treatment, can improve endothelial function and decrease oxidative stress, thus contributing to a decline of cardiovascular disease risk in type 2 diabetic patients.…”
Section: Cardiovascular Datamentioning
confidence: 99%
“…in vitro through good control of postprandial glucose levels, in agreement with previous data (Ceriello, 2004;Gomes et al, 2004;Gross et al, 2003).…”
Section: Meglitinidessupporting
confidence: 81%
“…The resultant hyperglycemia exerts its detrimental effects on endothelial function through different pathways, most of which result in impaired NO production (108). A laboratory study (112) in rabbit reports that even 3 h of high blood glucose can injure the macro-and microvasculature, as measured by endothelium dependent vasodilation. Chronic psychological stress can also lead to intracellular structural changes, which in turn aggravate hyperglycemia.…”
Section: Cortisolmentioning
confidence: 99%